Supporting information for InP-InxGa1-x as core-multi-shell nanowire quantum wells with tunable emission in the 1.3 – 1.55 μm wavelength range - Fonseka, H. A.; Ameruddin, A. S.; Caroff, P.; Tedeschi, D.; De Luca, M.; Mura, F.; Guo, Y.; Lysevych, M.; Wang, F.; Tan, H. H.; Polimeni, A.; Jagadish, C. (The Royal Society of Chemistry, 2017)
Section 1: Experimental details pertaining to the growth of InP- InxGa1-xAs QWs InP nanowire core: The InP nanowire cores were seeded by 50 nm colloidal Au particles. The Au particle-deposited InP (111)B substrates were heated to the growth temperature of 450˚C. Substrates were not annealed prior to growth, but TMIn was pre-flown for 15 s before initiating the growth. This pre-flow step reduces the non-vertical nanowire growths that arise from lack of alloying when the pre-growth annealing step is avoided. The TMIn and PH3 flows were 1.62 × 10-5 and 5 × 10-3 mol/min, respectively. Nanowire core growth was carried out for 30 min at 100 mbar reactor pressure. InxGa1-xAs QWs: After the core growth, the temperature was ramped up to the shell growth temperature of 550˚C and the reactor pressure was ramped to 180 mbar which was the pressure normally used in the current MOVPE system for InP-related planar vapour-solid epitaxial growth. The nanowire core was annealed for 3 min before depositing a thin InP buffer layer on the nanowire side facets in order to ensure a high quality surface for the subsequent QW growth. After a growth interruption of 5 s the QW growth was initiated. The TMIn, TMGa and AsH3 flows used for the study of the effect of QW thickness variation were 6.75 × 10-6, 5.51 × 10-6 and 1.34 × 10-3 mol/min, respectively, giving a vapour phase In molar fraction Xv = [TMIn]/([TMIn]+[TMGa]) of 0.55. The QW growth time was varied between 20 to 180 s depending on the targeted QW thickness. For the study of QW composition variation, the TMIn flow was kept constant at 6.75 × 10-6 mol/min while varying the TMGa flow to achieve compositions between GaAs and InAs, except in the case of GaAs, where the TMIn source was turned off. The growth time of these composition-varied QWs were also scaled accordingly in order to achieve a nominal thickness of 7 nm. Another 5 s growth interruption was included after the QW growth with AsH3 left on in order to prevent As desorption from the thin QW 1. Lastly, an InP barrier shell was grown for 12 min. For the growth of MQW structure, the QW, interruption and barrier growth steps were repeated two times more.